2021
DOI: 10.1002/chem.202102668
|View full text |Cite
|
Sign up to set email alerts
|

C−C Cross‐Couplings from a Cyclometalated Au(III) CN Complex: Mechanistic Insights and Synthetic Developments

Abstract: In recent years, the reactivity of gold complexes was shown to extend well beyond π-activation and to hold promises to achieve selective cross-couplings in several CÀ C and CÀ E (E = heteroatom) bond forming reactions. Here, with the aim of exploiting new organometallic species for crosscoupling reactions, we report on the Au(III)-mediated C-(sp 2 )À C(sp) occurring upon reaction of the cyclometalated complex [Au(C CH2 N)Cl 2 ] (1, C CH2 N = 2-benzylpyridine) with AgPhCC. The reaction progress has been monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 92 publications
2
5
0
Order By: Relevance
“…Changes to the absorption peak at 280 nm and the formation of a peak at 570 nm were observed by the 1 h time point, which remained unaltered until about 56 h. To further characterize this phenomenon, we used LC/ESI-MS to elucidate any potential speciation (Figure b) and found that, upon incubation of 1 with l -GSH, a reductively eliminated product of arylpyridine covalently linked to l -GSH through a C–S bond ( 1 –GSH, m / z 475) forms together with intact complex 1 ( m / z 670.2). It must be noted that cyclometalated Au­(III) complexes of the C^N archetype can undergo reductive elimination to form C–S arylated products induced by thiol nucleophiles such as cysteines and proteins , or direct C–N reductive elimination from Au­(III) . Whereas the C–S transformation has been a useful bioorthogonal strategy in biological systems and important for target engagement by Au compounds, a careful balance of the reactivity and stability is needed for therapeutic development, making ligand tuning an important descriptor in Au-based probe/drug discovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to the absorption peak at 280 nm and the formation of a peak at 570 nm were observed by the 1 h time point, which remained unaltered until about 56 h. To further characterize this phenomenon, we used LC/ESI-MS to elucidate any potential speciation (Figure b) and found that, upon incubation of 1 with l -GSH, a reductively eliminated product of arylpyridine covalently linked to l -GSH through a C–S bond ( 1 –GSH, m / z 475) forms together with intact complex 1 ( m / z 670.2). It must be noted that cyclometalated Au­(III) complexes of the C^N archetype can undergo reductive elimination to form C–S arylated products induced by thiol nucleophiles such as cysteines and proteins , or direct C–N reductive elimination from Au­(III) . Whereas the C–S transformation has been a useful bioorthogonal strategy in biological systems and important for target engagement by Au compounds, a careful balance of the reactivity and stability is needed for therapeutic development, making ligand tuning an important descriptor in Au-based probe/drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…The resurgence of gold (Au) chemistry over the past two decades has contributed to the development of synthetic methods, catalytic transformations, , materials for electronics, , reagents for bioorthogonal reactions, protein modifications, , and therapeutic agents. In the context of drug discovery, great impetus is derived from auranofin, a Food and Drug Administration (FDA)-approved drug for treating rheumatoid arthritis . Although Au­(III) complexes are highly valent and present opportunities for ligand tuning due to having more coordination sites than conventional linear Au­(I), the instability of Au­(III) has been its Achilles’ heel.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies carried out during the 1970s revealed that reductive elimination in square planar Au­(III) complexes can occur (a) through tricoordinate intermediates formed after ligand dissociation or (b) directly from the tetracoordinate complexes (Scheme A). , Alternatively, a concerted mechanism where C–C and B–F bonds form simultaneously has been proposed for the reaction of Au­(III) alkyl fluorido complexes with arylboronic acids (Scheme B) . Whereas the experimental evidence of pathways (a) , and (b) , is abundant for C–C coupling reactions, mechanistic data on reductive elimination processes leading to the C–heteroatom bond formation are scarce. The available information has been obtained on the dissociative reductive eliminations of alkyl, , aryl, , or trifluoromethyl halides and nondissociative reductive eliminations of ArX derivatives (X = NR 2 , PR 3 + , OR, SR, halogen). …”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 Alternatively, a concerted mechanism where C–C and B–F bonds form simultaneously has been proposed for the reaction of Au(III) alkyl fluorido complexes with arylboronic acids ( Scheme 1 B). 35 Whereas the experimental evidence of pathways (a) 32 34 , 36 39 and (b) 35 , 40 48 is abundant for C–C coupling reactions, mechanistic data on reductive elimination processes leading to the C–heteroatom bond formation are scarce. The available information has been obtained on the dissociative reductive eliminations of alkyl, 49 , 50 aryl, 38 , 51 or trifluoromethyl halides 52 and nondissociative reductive eliminations of ArX derivatives (X = NR 2 , PR 3 + , OR, SR, halogen).…”
Section: Introductionmentioning
confidence: 99%
“…These recent studies and the peculiar behavior of gold stimulated renewed interest for C–C and C–X reductive elimination from Au­(III) complexes. Besides experimental investigations, thorough density functional theory (DFT) studies have shed light into the factors influencing C–C coupling at gold. − , In general, two different scenarios can be distinguished depending on the hybridization of the carbon centers to couple. While C­(sp 2 )–C­(sp 2 ) reductive eliminations proceed readily from 4-coordinate Au­(III) complexes, C–C­(sp 3 ) reductive eliminations are more difficult to achieve and typically involve 3-coordinate Au­(III) species (Figure a).…”
Section: Introductionmentioning
confidence: 99%